Efficacy of the growing rod technique on kyphotic early-onset scoliosis - Cao, Jiang; Zhang, Xuejun; Cao, Jun; Gao, Rongxuan; Guo, Dong (Frontiers in Pediatrics, 2022)
Objective To explore the application of the growing rod (GR) technique in the treatment of kyphotic early-onset scoliosis (KEOS) and analyze its surgical efficacy and safety. Methods The clinical data of 30 children with KEOS who received GR treatment at our department between January 2016 and December 2019 were analyzed retrospectively. There were 18 cases with normal kyphosis (normal kyphosis group) and 12 cases with excessive kyphosis (excessive kyphosis group). Both groups received GR treatment, and all patients received anteroposterior and lateral spine X-ray examinations before, after the initial surgery, and at the final follow-up. The surgical conditions and imaging parameters of the two groups were compared, and the complications were recorded. Results There was no statistical difference in the Cobb angle of the major curve, apical vertebral translation (AVT), and trunk shift (TS) between the two groups before, after the first surgery, and at the final follow-up (P > 0.05). The Cobb angle of the major curve, the AVT, and the TS in both groups after the first surgery were lower than before the first surgery (P < 0.05), but there was no statistical difference between the two groups (P > 0.05). At the final follow-up, there were increases in both the Cobb angle and the AVT (P < 0.05), while the TS decreased in comparison with findings after the first surgery (P < 0.05). Before and after the first surgery and at the final follow-up appointment, there was a statistical difference in the degree of thoracic kyphosis (TK) between the two groups (P < 0.05), while there was no statistical difference in terms of lumbar lordosis (LL), the proximal junctional angle (PJA), and the distal junctional angle (DJA) (P > 0.05). After the first surgery, TK and LL showed a significant moderate response in both groups (P < 0.05), while there was no significant difference in TK, LL, PJA, and DJA compared with the results at the final follow-up (P > 0.05). Conclusions The use of the GR technique can improve kyphosis in KEOS treatment.